Kebiasaan makanan ikan lidah (Cynoglossus lingua) di perairan ujung pangkah, gresik, jawa timur - . Sulistiono; Citra Sari; Murniarti Brodjo (Jurnal Ilmu Pertanian Indonesia, 2009)
One of an fishery commodity in Ujung Pangkah is flatfish ( Cynoglossus lingua). This study was conducted in Ujung Pangkah waters, Gresik, East Java using fish samples (N=94 males, N=108 females) collected during August 2005 to January 2006. The Study aimed to investigate food habits of the flat fish caught in the area. Research result shows that shrimps was a main food, while crab and Bivalva were complementary food both for male and female fish. Based on index of stomach contents, the index was higher during September for male, and August for female fish. Kinds and percentage of stomach contents varied according to size both for male and female. Therefore, the main food of the male and female fish was simmilar (e.g. shrimps) According to simmilariy index, food habit of the male and female fish is simmilar.